2021
DOI: 10.1038/s42255-021-00341-7
|View full text |Cite|
|
Sign up to set email alerts
|

Diet-dependent regulation of TGFβ impairs reparative innate immune responses after demyelination

Abstract: Multiple sclerosis (MS) is one of the most common causes of chronic disability in young adults. In 85% of the cases, the disease starts with a relapsing-remitting course but, as age advances, the majority of patients enter a progressive phase of the disease characterized by neurological decline and brain atrophy. Treatments that delay, prevent or reverse this progression phase are an unmet need in MS research. The cause of progressive MS is not known, but remyelination failure may contribute. Hence, large effo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 382 publications
1
38
0
Order By: Relevance
“…The density of IBA1 + phagocytes was higher in ALOX15-deficient mice compared to control ( Figures 3 D and 3H). In addition, KO mice showed an increase of phagocyte-associated myelin debris and increased crystal formation ( Figures 3 F, 3I, and 3J), which is associated with dysfunctional cholesterol clearance, persisting inflammation, and impaired remyelination ( Bosch-Queralt et al., 2021 ; Cantuti-Castelvetri et al., 2018 ). In accordance, the percentage of CC1 + OLIG2 + mature oligodendrocytes was slightly reduced in ALOX15-deficient mice, while the total densities of OLIG2 + oligodendrocyte lineage cells were equal ( Figures 3 G, 3K, and S3 C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The density of IBA1 + phagocytes was higher in ALOX15-deficient mice compared to control ( Figures 3 D and 3H). In addition, KO mice showed an increase of phagocyte-associated myelin debris and increased crystal formation ( Figures 3 F, 3I, and 3J), which is associated with dysfunctional cholesterol clearance, persisting inflammation, and impaired remyelination ( Bosch-Queralt et al., 2021 ; Cantuti-Castelvetri et al., 2018 ). In accordance, the percentage of CC1 + OLIG2 + mature oligodendrocytes was slightly reduced in ALOX15-deficient mice, while the total densities of OLIG2 + oligodendrocyte lineage cells were equal ( Figures 3 G, 3K, and S3 C).…”
Section: Resultsmentioning
confidence: 99%
“…Ideally, the inflammatory innate response is self-limiting, and the phagocytic infiltrate declines over time. With increasing age or obesity, however, the response can become maladaptive and impede remyelination ( Bosch-Queralt et al., 2021 ; Cantuti-Castelvetri et al., 2018 ; Chiurchiù et al., 2018 ). Using a systems biology approach combining proteomics and lipidomics, we characterized lipid pathways and lipid mediators that are upregulated in demyelinating lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, both PD patients and experimental animal models of PD exhibit abnormal lipid accumulation in dopaminergic neurons and their surrounding microglia, but have a reduced lipid load in adjacent astrocytes. One recent study found that a Western diet impairs recovery from demyelinating injuries, by inhibiting microglial phagocytosis and clearance of lipid debris ( 25 ). Another study found that in the setting of demyelination, microglia synthesize desmosterol, the immediate cholesterol precursor and liver X receptor (LXR) agonist, and that microglial sterol synthesis is essential for efficient remyelination ( 26 ).…”
Section: Lipid Metabolism In the Brainmentioning
confidence: 99%
“…A number of agonistic anti-TREM2 antibodies were recently developed (Cheng et al, 2018;Cignarella et al, 2020;Ellwanger et al, 2021;Fassler et al, 2021;Price et al, 2020;Schlepckow et al, 2020;Wang et al, 2020), which either enhance cell-surface levels of signaling competent TREM2 by blocking TREM2 shedding and/or crosslink TREM2 receptors to stimulate downstream signaling via Syk phosphorylation. In preclinical studies these antibodies boost protective functions of microglia as shown by enhanced amyloid ßpeptide (A ß) and myelin clearance, reduced amyloid plaque load, improved memory in models of amyloidosis, and support of axon regeneration and remyelination in models of demyelinating disorders such as multiple sclerosis (Bosch-Queralt et al, 2021;Cheng et al, 2018;Cignarella et al, 2020;Ellwanger et al, 2021;Fassler et al, 2021;Lewcock et al, 2020;Price et al, 2020;Schlepckow et al, 2020;Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%